Taboo Topics in Cat on a Hot Tin Roof and A Streetcar Named Desire by Tennessee Williams - Humlová, Monika (Univerzita Pardubice, 2011)
The work is focused on the plays Cat on a Hot Tin Roof and A Streetcar Named Desire by the American playwright Tennessee Williams, and the articulation of topics that were not entirely common for a dramatic production of the period. After setting of both plays into the socio-cultural context with the special emphasis on the atmosphere of the post-war years in the United States of America and a stand of the society on the so-called taboo topics, this issue is addressed in the above mentioned dramatic texts.
Tabuizovaná témata v dílech Kočka na rozpálené plechové střeše a Tramvaj do stanice Touha od Tennesseeho Williamse
Keywords: Spojené státy americké; období po druhé světové válce; americké drama; tabuizovaná témata; rodina; cenzura; United States of America; post-Second World War period; American drama; taboo topics; family; censorship